Effect of freeze-dried powder of lactic acid bacteria treatment of pediatric bacterial peritonitis on immune function and nutritional status - Xue, Yang; Zhang, YuTing (European journal of medical research, 2025)
This study was to investigate the effects of freeze-dried powder of lactic acid bacteria treatment of pediatric bacterial peritonitis on immune function and nutritional status. 100 cases of bacterial peritonitis children from September 2020 to September 2021 were included and divided into a control group and an observation group using a randomized numerical table, with each group containing 50 cases. The control group was given routine treatment such as antimicrobial drugs, and the observation group was given adjuvant treatment of freeze-dried powder of lactic acid bacteria. The clinical efficacy, immune function, nutritional status, inflammatory response, intestinal dysbiosis, and endotoxin level were compared between the two groups. The total clinical effective rate of the observation group was higher than that of the control group. The ratio of CD3 , CD4 , and CD4 /CD8 and the levels of ALB, TP, and Hb after treatment of the observation group were higher than those of the control group. CRP, PCT, and MCP-1 of the observation group were lower than those of the control group after treatment. Intestinal flora dysbiosis in the observation group was attenuated, and endotoxin level was reduced compared to the control group. No drug-related adverse reactions were observed in both groups during treatment. Freeze-dried powder of lactic acid bacteria can improve immune function and nutritional status, as well as reduce inflammatory response and intestinal flora dysbiosis in pediatric bacterial peritonitis.